Posisi dan Pencapaian Wisran Hadi dalam Arena Sastra Indonesia - Lastry Monika (Balai Bahasa Sumatera Utara, 2021)
Wisran Hadi is known as a man of letters and an expert in culture who has produced works in various genres. During his career, the works he produced not only received a number of awards, but also caused controversy from his own community group in the Minangkabau. In this regard, this research tries to examine the position and achievements of Wisran Hadi in the arena of Indonesian literature. The discussion includes the efforts made by the author to achieve a position, to operate in the literary arena, and to maintain his position. Based on Pierre Bourdieu's theory of genetic structuralism, the results of the analysis show the following. First, the position of the literary arena occupied by Wisran Hadi is dominantly on the principle of an autonomous hierarchy, so that it tends to contradict the laws that apply in the arena of power The structure of the literary arena is a limited production arena. Second, the achievement of positions based on habitus, artistic practice, the acquisition and exchange of symbolic capital, the acquisition of awards, and the survival of the Bumi Teater group. Third, practices and strategies in maintaining position are by producing works in various genres, prioritizing exploration of words and languages, and elaborating classic works such as kaba, tambo, and history. In addition, the work is positioned based on various elements such as habitus, the structure of the arena occupied, the position in the arena, to the situation and conditions of social reality that are the source and target of the work.